Kajian Literatur Penilaian Guru terhadap Keterampilan Siswa dalam Membaca Puisi Tahun 2015—2021 - Amanda Maharani; Nabila Nufaiza Yusuf; Yeti Mulyati; Yunus Abidin (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The teacher's assessment of students' poetry reading skills has differences in research instruments, especially in the assessment aspect. The assessment instrument used in poetry reading skills is adjusted to the elements contained in the poem. This study aims to describe the literature review of the instruments used in poetry reading assessment. This study used a qualitative method with a literature review approach. The research stages were carried out starting from article collection, article reduction, article display, discussion, and conclusion. Sources of research data are in the form of national articles in the last 6 years (2015-2021). The results showed that the aspect that was often assessed was the aspect of intonation with a percentage of 21%, while the aspect that was rarely used was the aspect of articulation, interpretation and stage mastery with a percentage of 1%. There was also an addition to the assessment aspect of poetry reading from year (2015-2021).